Vision- driven strategies and policies for managing educational systemic change: a qualitative analysis - Ghavifekr, Simin; Afshari, Mojgan; Siraj, Saedah; Razak, Ahmad Zabidi Abdul (American-Eurasian Network for Scientific Information, Jordan, 2013)
Vision has been considered as a major element in leadership and strategic planning which is referring to all organizations including education.In managing educational change process, planning and producing vision-driven strategies and policies by the leaders and management teams, not only enhance the quality of organizational performance, but also ensure the dynamic implementation of change process. In this regard, formulating an appropriate and effective “vision” means examining and re-examining the strategic planning for the organization as well as making clear the purpose of change for the management. As a result, the importance of vision-driven strategies and policies in an educational organization would be more essential when the organization facing a new technologybased change. This is because implementation of such a change would affect all levels of the educational organization from various aspects which is called “systemic change”. The main purpose of this paper is to examine “vision” as one of the main component of educational change management to see the various aspects of visionary planning in situation of systemic change in an Open and Distance Learning (ODL) organization in Malaysia. From the data analysis for this qualitative study, it was found that planning, organizing, guiding, and monitoring are the main four vision-driven strategies and policies for the management in the context of a technology-based change or systemic change. Moreover the results show that vision and strategic planning play as the two key prerequisites for the success of the educational systemic change. The results of in-depth analysis for “vision” as the key theme and planning, organizing, guiding and monitoring as the four sub-themes as well as the emerged sub-sub-themes are presented in this paper